Rise & shine, Benedict Stone [large type] - Patrick, Phaedra (Thorndike Press, 2017)
In the village of Noon Sun, Benedict Stone has settled into a predictable routine. Business at his jewelry shop has dried up; his marriage is on the rocks. His life is in desperate need of a jump start. And then a surprise arrives at his door. Gemma is Benedict's audacious niece - the daughter of his estranged brother, Charlie. The two brothers haven't spoken in almost two decades, since Charlie left for America. Reckless and stubborn, Gemma invites herself into Benedict's world and turns his orderly life upside down. But she might just be exactly what he needs to get his life back on track.